The blockchain-enabled technology and carbon performance: Insights from early adopters - Fernando, Yudi; Nor Hazwani, Mohd Rozuar; Mergeresa, Fineke (Elsevier Publisher, 2021)
This paper examined the drivers of blockchain technology adoption and carbon performance using the theory of technology-organization-environment (TOE) as the basis for the development of a technology adoption framework. Blockchain technology has passed the proof testing phase and is attracting early adopters who can gain benefits from it. Manufacturing firms that had adopted the blockchain technology and voluntary reported the carbon emission were targeted as the sample and survey data were collected from manufacturing firms that were registered with the Association of Malaysian Manufacturers. Unfavourable support of top management and the lack of technology competence were the main barriers to the adoption of blockchain technology among manufacturing firms. The results indicate that firms did not achieve low carbon performance and that a lack of pressure from competitors and technical competency to undertake blockchain technology were factors. No evidence existed demonstrating a linkage of early adopters of blockchain technology with and low carbon performance. Recommendations of this study include that firms should take the initiative to record the energy consumption, engage in the transfer of carbon credits, and monitor carbon performance using reliable technology to improve business transparency and sustainability.